ASSISTANCE OF MSMES OF GENDONGAN VILLAGE, TINGKIR SUBDISTRICT, SALATIGA CITY, THROUGH DIGITAL MARKETING - Widyakto, Adhi; Suryawardana, Edy; Susanto, Susanto (Indonesian Journal of Devotion and Empowerment, 2021)
The purpose of this community service activity is to help increase sales for MSMEs in Gendongan Village who are affected by the COVID 19 pandemic. With this pandemic condition, MSMEs are required to survive to avoid bankruptcy. The method used in this community service activity provides direct Training with tutorials in the field by teaching how to apply digital marketing or online marketing. The expected result is that the MSME product market in Gedongan Village gets a broader market reach, of course, with recognizable and easily accessible products by consumers. Tujuan kegiatan pengabdian masyarakat ini yaitu untuk membantu meningkatkan penjualan bagi UMKM di Kelurahan Gendongan yang terdampak pandemi COVID 19. Dengan adanya kondisi pandemi ini maka UMKM di tuntut untuk bertahan agar terhindar dari kebangkrutan. Metode yang digunakan dalam kegiatan pengabdian kepada masyarakat ini yaitu dengan memberikan pelatihan secara langsung dengan tutorial di lapangan dengan mengajarkan cara menerapkan digital marketing atau pemasaran online. Hasil yang diharapkan yaitu pasar produk UMKM di Kelurahan Gedongan mendapatkan jangkauan pasar yang lebih luas tentunya dengan produk yang dikenali dan mudah di akses oleh konsumen.